(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the strategic deployment of ethnographic realia—culturally specific symbols, traditions, and historical references—in the political rhetoric of Vladimir Putin, Shavkat Mirziyoyev, and Donald Trump. Through a comparative critical discourse analysis of speeches, public performances, and digital media content, the research reveals how these leaders employ cultural realia to construct narratives of national identity, legitimize authority, and mobilize political support. Findings demonstrate that while the specific symbols differ—Putin’s use of Orthodox and Soviet imagery, Mirziyoyev’s revival of Timurid heritage, and Trump’s nostalgic Americana—their rhetorical functions remain consistent: authenticating leadership, demarcating in-group boundaries, and evoking emotional responses. The study introduces the concept of "rhetorical palimpsests" to describe how political actors layer contemporary meanings over traditional symbols while retaining their affective power. By bridging political communication theory with cultural semiotics, this research contributes to understanding how nationalist rhetoric adapts to different cultural contexts while employing similar persuasive mechanisms. The conclusions underscore the enduring significance of cultural memory in politics while raising critical questions about its instrumentalization in an era of increasing polarization and digital mediation.